Shear Performance of ULCC and PCC: Experimental and Numerical Insights Using DIC and FEM - Tajunnisa, Yuyun; Mansur, Moh Safii; Suprobo, Priyo; Apsari, Auliagitta K.; Sutrisno, Wahyuniarsih (Civil Engineering Journal, 2025)
This study investigates the shear behavior of reinforced concrete beams constructed with high-calcium fly ash-based Ultra-Low Carbon Concrete (ULCC) as a sustainable alternative to conventional Portland Cement Concrete (PCC). The objective is to assess ULCC’s structural performance under shear and its potential as a low-carbon substitute. Using a dry-mix method with dry activators, six beams (five ULCC, one PCC) of identical dimensions (150 × 250 × 1800 mm) were tested under four-point bending, with variations in shear reinforcement, flexural reinforcement, and shear span-to-depth (a/d) ratios. Digital Image Correlation (DIC) was employed to monitor crack propagation and strain development, while Finite Element Modeling (FEM) provided numerical validation. Results show that increasing shear reinforcement enhanced capacity by 12.05%, whereas higher (a/d) ratios decreased it by 22.63%; increased flexural reinforcement improved shear resistance by 31.27%. FEM closely matched experimental outcomes, with a load-deflection ratio of 1.01. ULCC outperformed PCC in shear capacity and exceeded ACI 318-19 predictions. The integration of DIC and FEM offers a comprehensive analysis framework, and the findings demonstrate ULCC’s viability as a structurally efficient, environmentally sustainable alternative for shear-critical applications.